2008
DOI: 10.1159/000128282
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Eruptive Giant Mollusca Contagiosa in an Adult Psoriasis Patient during Efalizumab Therapy

Abstract: Molluscum contagiosum is a common viral skin infection in children with atopic diathesis and not rare in HIV patients. We report a 45-year-old psoriasis patient who developed eruptive mollusca contagiosa during an antipsoriatic treatment with efalizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…The typical appearance of multiple discrete skin‐colored umbilicated papules is easily recognizable. Disseminated lesions may be seen in patients receiving systemic immunosuppression 1 and can localize to skin receiving topical immunosuppressive medication 2 . In patients with HIV, widespread lesions and more unusual presentations, including a cheek abscess, have been reported 3 …”
Section: Discussionmentioning
confidence: 99%
“…The typical appearance of multiple discrete skin‐colored umbilicated papules is easily recognizable. Disseminated lesions may be seen in patients receiving systemic immunosuppression 1 and can localize to skin receiving topical immunosuppressive medication 2 . In patients with HIV, widespread lesions and more unusual presentations, including a cheek abscess, have been reported 3 …”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of multiple MCs during treatment with PSL, MTX, and biologics has been reported [1][2][3][4][5][6], and a few cases of multiple MCs in patients with RA have also been seen [5,6]. A number of studies have shown immunologic dysfunction in RA.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the postmarketing surveillance different and severe cases of opportunistic infections have been reported including sporadic case reports of visceral leishmaniasis, disseminated eruptive giant molluscum contagiosum, cytomegalovirus colitis and fatal cases of progressive multifocal leukoencephalopathy [36,37,38,39,40]. At the time this paper was resubmitted, the European Medicines Agency recommended withdrawal of the marketing authorization for efalizumab as the risks outweighed its benefits [40].…”
Section: Discussionmentioning
confidence: 99%